Medication Dispenser Device

JP7599236B2Active Publication Date: 2024-12-13PORTAL MEDICAL
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023127760
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-10-31
Filing Date
2023-08-04
Publication Date
2024-12-13
Estimated Expiration
2038-10-29

AI Technical Summary

Benefits of technology

【0010】 上記炭素層における架橋は、少なくとも80%、好ましくは少なくとも90%、より好ましくは少なくとも95%でもよい。この高い架橋密度は、コーティングの完全性を改善し、薬剤の沈着された層への移動及び沈着された層による吸収を著しく低減する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599236000004
    Figure 0007599236000004
  • Figure 0007599236000005
    Figure 0007599236000005
  • Figure 0007599236000006
    Figure 0007599236000006
Patent Text Reader

Abstract

To provide an improved dispenser device for dispensing a medicament.SOLUTION: A dispenser device 10 comprises at least one component having a coating that comes into contact with a medicament during storage or use of the device on at least one surface thereof. The coating comprises a cross-linked non-diamond like carbon layer comprising 50 atom% or less of hydrogen and having an interface with the underlying surface of the component.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to dispenser devices for dispensing medicaments, methods for manufacturing them, components thereof and methods for processing these components, with particular, but not necessarily exclusive, reference to dispenser devices for dispensing inhaled medicaments. [Background technology]

[0002] It is well known to administer medication to a patient by inhalation, typically using a pressurized dispenser device that dispenses the medication in a carrier fluid and / or propellant as an aerosol. Such devices are often referred to as pressurized metered dose inhalers (pMDIs) and are most commonly used to treat asthma and chronic obstructive pulmonary disease (COPD).

[0003] A problem with this type of dispenser device is the absorption or adverse interactions (undesirable chemical reactions) of the active agent on the internal surface of the device. This can eventually lead to loss of efficacy and / or inconsistent dosing during storage of the device or between doses. In some cases, clustering of drug particles can occur when the active agent is present as a suspension of particles. One approach that has been used to reduce surface absorption of the active agent is to modify the surface properties of the device, which has traditionally been done by spray coating with low energy polymers. However, this process can be difficult to control and often the quality of the surface coating is variable. Long chains of polymeric materials with very little cross-linking tend to deposit on the surface of the device, requiring a relatively thick polymer layer (on the order of 5 microns to 100 microns) to provide an effective barrier to the drug. This type of spray coating polymer typically has less than 10% cross-linking, usually significantly less than 5% cross-linking. The inventors have realized that by increasing the cross-link density of the barrier, the effectiveness of the barrier can be improved, especially at thinner thicknesses at the sub-micron level.

[0004] One approach that has been used to reduce surface absorption of active drugs by increasing the crosslink density of the barrier is to deposit a low energy polymer or inorganic coating (or a combination of the two) by plasma polymerization. US Pat. No. 5,399,433 and US Pat. No. 5,499,446 are examples of prior art documents that disclose plasma polymerization on various components of dispenser devices. However, it has been recognized that there can be a number of delivery problems with this type of coating. One of the problems relates to devices that use particulate suspensions as a delivery system. These delivery systems can be affected by adhesion of drug particles to these particulates and the "caking" of these particulates on the walls of the can or on other surfaces within the dispenser device. This can lead to agglomerations that affect the drug dose. A second problem is due to the autocatalytic decomposition of some drugs upon contact with certain materials, especially metal oxides such as aluminum oxide and magnesium oxide, and other reactions between the components and the drug, such as corrosion, or the formation of harmful chemical species due to such reactions. Certain components of dispenser devices, especially the can body, are formed from aluminum and therefore have an aluminum oxide surface layer that also contains alloy compounds such as magnesium. Metal oxide based materials contain metal ions available for mobility and interaction at just a few nanometers. In the case of native oxides, these ions are available near the surface at less than 5 nm. Coating such components with a barrier potentially offers a way to prevent both degradation and, in the case of non-stick barriers, adhesion of drug particles to the surface. However, it is not necessarily the case that degradation and / or corrosion is the only concern for a particular drug (e.g., when the drug is in a solution delivery system and not in suspension). It is not necessary for the coating to have adhesive properties. Furthermore, the performance of some coatings may not be optimal for a variety of reasons. One such reason is that the coating may have flaws or cracks that allow drug molecules present in the solution to reach the surface of the component parts, such as the aluminum oxide surface of a can. This is because the coating may have small pores where decomposition and / or corrosion can occur. Conversion processes such as anodizing do not address the issue, as oxide levels will increase and migration paths will form.

[0005] Most prior art methods of plasma polymerization on the surfaces of device components use fluorocarbon precursors to directly coat the internal surfaces of the device with fluorocarbon polymers. However, such techniques require high power densities (0.5 W / cm) that can be detrimental to the coating deposition rate. 3 ) is required because, while the ions are being deposited to form the coating, they are resputtered from the surface, causing unreacted sites to spontaneously react with the resulting free fluorine. This causes premature termination of the growing polymer chains, resulting in a porous powder-like coating with a maximum thickness that does not increase over time. Such coatings are indeed highly porous with separate terminated polymer chains, which may then be easily shed by solvent extraction or contact with, for example, hydrofluoroalkane (HFA) sprays due to their extremely low surface tension. As a result, the inventors have found that it is extremely difficult to deposit fluorocarbon polymer coatings with a crosslink density of more than 60% due to the nature of the self-etching effect in the plasma environment. Such films also show significant loss of hydrophobicity and / or water repellency, since the very nature of the crosslinking causes, for example, loss of CF2 groups associated with water repellency. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] European Patent No. 1066073 [Patent Document 2] International Publication No. 2008 / 146024 Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention, in at least some of its embodiments, addresses the problems and needs discussed above. [Means for solving the problem]

[0008] According to a first aspect of the present invention, there is provided a dispenser device for dispensing a drug, the device comprising at least one component having a coating on at least one surface thereof that will come into contact with the drug during storage or use of the device, the coating comprising a crosslinked non-diamond-like carbon layer that comprises 50 At% or less hydrogen and has an interface with the underlying surface of the component.This low atomic ratio of hydrogen is due to the high crosslink density in the carbon layer.The high crosslink density improves the integrity of the coating (i.e. reduces the occurrence of cracks or small holes in the coating that can cause corrosion of the component and / or decomposition of the drug).This also allows the coating to be deposited much thinner than prior art techniques while achieving high barrier properties.

[0009] In one embodiment, the carbon layer may contain up to 40 At% hydrogen, preferably up to 33 At% hydrogen, preferably up to 25 At% hydrogen, more preferably up to 20 At% hydrogen, even more preferably up to 10 At% hydrogen, and most preferably up to 5 At% hydrogen. As discussed above, it is preferred to reduce the atomic ratio of hydrogen in the carbon layer by increasing the crosslink density and thereby increasing the At% of carbon.

[0010] The crosslinking in the carbon layer may be at least 80%, preferably at least 90%, more preferably at least 95%. This high crosslink density improves the integrity of the coating and significantly reduces drug migration into and absorption by the deposited layer.

[0011] In a preferred embodiment, the carbon layer has a thickness of 5 nm to 150 nm, preferably 50 nm to 150 nm.

[0012] Suitably, the carbon layer may contain less than about 3 At%, preferably less than about 2 At%, more preferably less than about 1 At% oxygen as measured by X-ray photoelectron spectroscopy (XPS). In general, the oxygen At% should be as close to zero as possible for the process and stage of the precursors and metals used. In this way, the possibility of decomposition of the agent is minimized and anti-corrosion performance is maximized by ensuring both complete coverage (oxygen is not detected from the underlying oxide by XPS) and non-reactivity / attraction to polar oxygen functional groups in the coating.

[0013] The coating may include a second layer that will come into contact with the drug during storage or use of the device. In such embodiments, the carbon layer acts as a base barrier layer interfacing with the surface of the component, and the second layer provides a barrier layer for drug contact. Acting as a top layer, the carbon base layer provides a uniform insulating layer that masks any non-uniformities on the component surface.

[0014] Suitably, the second layer may be hydrophobic. The second layer may be a polymeric layer or an inorganic layer. Preferably, the second layer is a plasma polymerized polymeric layer.

[0015] The second layer can be a fluorocarbon polymer layer, such as, but not limited to, a perfluorocarbon layer. The interior surface after application of the carbon layer is functionalized with either plasma-derived C ions or by reaction with fluorine ions resulting in a plasma-functionalized surface. x F y Either deposition of ions can utilize a uniform floating potential or charge that allows a uniform thin film of fluorocarbon to be formed. This results in a hydrophobic, water-repellent surface with low surface energy and high barrier properties.

[0016] In embodiments where the second layer is a fluorocarbon polymer layer, the fluorocarbon polymer layer has a fluorine to carbon ratio of 1:1 to 1.95:1. The fluorine to carbon ratio is preferably 1.25:1 to 1.8:1. This fluorine to carbon ratio is higher than that typically observed in straight plasma fluorocarbon coatings (i.e., without a carbon underlayer interacting with the surface of the component).

[0017] The second layer may have a thickness of 1 nm to 100 nm, preferably 1 nm to 60 nm, more preferably 1 nm to 25 nm, and most preferably 1 nm to 15 nm. The carbon layer allows a thin fluorocarbon film to be deposited, with the underlying carbon film providing the desired barrier properties that a fluorocarbon film of the same thickness would never provide. Thus, a thin coating of high integrity can be achieved.

[0018] Advantageously, the fluorocarbon polymer layer may contain less than about 2 At%, preferably less than about 1 At%, and more preferably less than about 0.9 At% oxygen as measured by XPS. As mentioned above, it is preferred to have as low an At% as possible in the coating, thereby minimizing the possibility of drug degradation and maximizing anti-corrosion performance.

[0019] In one embodiment, the second layer has an interface with the carbon layer. In the present invention, the interface between the carbon layer and the second layer is graded. This grading results in a highly covalently intact structure that exhibits inherently strong cohesive strength properties that are impermeable to HFA and other organic solvents. The gradient of carbon therethrough preferably exceeds a step thickness of 1 nm to 75 nm, more preferably 1 nm to 40 nm, and most preferably 1 nm to 15 nm.

[0020] The coating may have a water contact angle of 115 degrees to 130 degrees, and therefore the coating has a highly water-repellent hydrophobic surface.

[0021] Preferably, the crosslinking in the second layer is 75% to 35%.

[0022] The dispenser device may be in the form of a pressurized dispenser device that dispenses the medicament in a carrier fluid. For example, the dispenser may be a pressurized metered dose inhaler. At least one component may be a metal component or a polymeric component. The component may be a metal can body. However, other components of the dispenser device, such as a valve stem and a spring, are also included.

[0023] In one embodiment, at least one component is formed from aluminum. In a particularly preferred embodiment, the metal component is an aluminum can body. Alternatively, the metal component may be formed from stainless steel.

[0024] In embodiments in which at least one component is formed of aluminum, preferably at least one surface having the coating thereon does not turn black upon exposure to acidified copper sulfate. Aluminum turns black upon exposure to acidified copper sulfate due to reaction with aluminum / aluminum oxide, causing copper deposition at the reaction sites (small pores in otherwise exposed areas). Thus, at least one surface having the coating thereon does not react with acidified copper sulfate and exhibits high integrity without small pores.

[0025] In one embodiment, the at least one component is a can body, the interior surface of the can body having the coating described above.

[0026] Preferably, the medicament is an inhaled medicament.

[0027] According to a second aspect of the present invention there is provided a component for a dispenser device comprising a coating on at least one surface thereof which comes into contact with the medicament during storage or use of the device, the coating comprising a crosslinked non-diamond-like carbon layer comprising up to 50 At% hydrogen and having an interface with the underlying surface of the component.

[0028] The various preferred features and options of the first aspect apply to the second aspect as well, unless the context dictates otherwise.

[0029] According to a third aspect of the invention there is provided a method of treating a component of a medicament dispenser device comprising at least one surface which will come into contact with medicament during storage or use of the device, comprising the steps of: Providing the components; coating at least one of the surfaces with a coating comprising a crosslinked non-diamond-like carbon layer having a hydrogen content of 50% or less and having an interface with at least one surface of the device; A method is provided, comprising:

[0030] The carbon layer is preferably formed by a plasma treatment process which comprises generating a plasma of at least one hydrocarbon monomer having the formula C n H 2n+2 (wherein n is 1 to 12). Methane and ethane are particularly preferred. C3H8, C4H 10 and C5H 12 is also a preferred embodiment. Alkenes, alkynes and cyclic hydrocarbons may be used as precursors.

[0031] In a preferred embodiment, the coating comprises a second layer that comes into contact with the drug during storage or use of the device, the second layer being formed by plasma deposition. Suitably, the carbon layer may be directly associated with the second layer. Preferably, the interface between the carbon layer and the second layer is graded.

[0032] The plasma deposition of the second layer may include plasma polymerizing at least one monomer. The at least one monomer may be a fluorocarbon monomer, preferably a perfluorocarbon monomer. Suitable perfluorocarbon precursors include C n F 2n+2 (where n is in the range of 1 to 16, preferably in the range of 1 to 6), as well as the chemicals HFA134a (1,1,1,2-tetrafluoroethane) and HFA227 (1,1,1,2,3,3,3-heptafluoropropane), which are commonly used as propellants in drug dispenser devices. Other propellants such as HFA 152a (1,1-difluoroethane), R32 and hydrofluoroolefins (HFOs) may also be used. Cyclic or unsaturated perfluorocarbons may also be used. Particularly preferred embodiments are CF4 and C4F8. Small precursors are preferred, since the proportion of fluorine is greater and a greater number of CF2 groups can be formed.

[0033] The grading between the carbon layer and the second layer can be achieved by increasing the amount of fluorocarbon (or other) monomers that are plasma polymerized to form the second layer, while decreasing the amount of hydrocarbon monomers.

[0034] In one embodiment, at least a portion of the coating step is performed under DC bias control. Preferably, the plasma ionization of the at least one hydrocarbon monomer and the plasma deposition of the second layer are performed under DC bias control, with the plasma ionization of the at least one hydrocarbon monomer being performed using a higher DC bias voltage than the plasma deposition of the second layer. This prevents etching of the carbon layer, thus maintaining the coating integrity and high degree of cross-linking.

[0035] Preferably, the plasma deposition of the second layer is carried out using a DC bias voltage of less than 60 V, preferably less than 50 V, more preferably less than 40 V. A low DC bias voltage prevents etching of the carbon layer, thus maintaining coating integrity and a high degree of cross-linking.

[0036] Preferably, the plasma ionization of the at least one hydrocarbon monomer is carried out using a DC bias voltage of from 1 volt to 150 volts, preferably from 30 volts to 80 volts, more preferably from 50 volts to 75 volts.

[0037] In a preferred embodiment, at least a portion of the coating step is performed in the range of 0.01 W / cm 2 ~0.05W / cm 2 , preferably 0.02 W / cm 2 ~0.03W / cm 2 This low power density is beneficial to the coating deposition rate and to the coating integrity since there is no resputtering or etching of the coating which may otherwise cause termination of the growing polymer chains. .

[0038] Preferably, at least a portion of the coating step is performed using a 9×10 -1 mbar~2×10 0 It may be carried out using process pressures in the mbar range, which increases the deposition rate of the coating.

[0039] Preferably, the method further comprises a cleaning step prior to the coating step. This removes any pre-processing hydrocarbons or ubiquitous contaminants from the surface of the component and etches away any surface irregularities. , leaving the resulting surface clean and dramatically functionalized.

[0040] According to a fourth aspect of the invention there is provided a dispenser device for dispensing a medicament, the device comprising at least one component having a coating on at least one surface thereof, the coating comprising a carbon base layer having an interface with an underlying surface of the component and a second layer which comes into contact with the medicament during storage or use of the device.

[0041] According to a fifth aspect of the invention there is provided a component for a dispenser device, the component comprising a coating on at least one surface thereof, the coating comprising a carbon base layer having an interface with the underlying surface of the component and a second layer that comes into contact with the medicament during storage or use of the device.

[0042] Unless the context dictates otherwise, the various preferred features and options of the first and second aspects of the invention apply equally to the fourth and fifth aspects of the invention.

[0043] According to a sixth aspect of the invention there is provided a method of treating a component of a medicament dispenser device comprising at least one surface which will come into contact with medicament during storage or use of the device, comprising the steps of: Providing the components; coating at least one of said surfaces with a coating comprising a carbon base layer having an interface with the underlying surface of the component and a second layer that comes into contact with the agent during storage or use of the device; A method is provided, comprising:

[0044] The various preferred features and options of the third aspect of the invention apply equally to the sixth aspect of the invention, unless the context dictates otherwise.

[0045] According to a seventh aspect of the present invention there is provided a method of manufacturing a drug dispenser device comprising processing a component according to the method of the third or sixth aspect of the present invention, providing other components of the device and assembling these components to obtain an assembled drug dispenser device.

[0046] Embodiments of the present invention will now be described, by way of example only, with reference to the accompanying drawings, in which: [Brief description of the drawings]

[0047] [Figure 1] FIG. 2 is a cross-sectional view of a pressurized dispenser device. [Diagram 2] FIG. 1 shows an arrangement for coating a can body. [Figure 3A] FIG. 1 shows a cut aluminum can body that was subjected to a copper sulfate test and had a negative reaction with copper sulfate after 1 minute. [Figure 3B] FIG. 1 shows a cut-open aluminum can body subjected to a copper sulfate test and having a fine particle reaction with copper sulfate after 1 minute. [Figure 3C] FIG. 1 shows a cut-open aluminum can body that was subjected to a copper sulfate test and had a partial reaction with copper sulfate after 1 minute. [Figure 3D] FIG. 1 shows a cut-open aluminum can body that was subjected to a copper sulfate test and had a complete reaction with copper sulfate after 1 minute. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0048] 1 depicts a pressurized dispenser device, generally designated 10, comprising a housing 12 which houses a pressurized drug-containing mechanism 14. The housing 12 comprises an open cylindrical portion 12a in which the pressurized drug-containing mechanism 14 is disposed, and an open passageway 12b which serves as a mouthpiece. The housing 12 further comprises an inner wall 12c which supports a socket 12d having a passageway 12e which houses a valve stem of the pressurized drug-container mechanism. The passageway 12e communicates with an opening 12f which in turn communicates with an outlet passageway defined by the open passageway 12b. The inner wall 12c is formed with a number of openings 12g which allow air to flow from an upper region of the housing 12 to the open passageway 12b.

[0049] The structure and operation of pressurized drug container mechanism 14 will now be described in more detail. Mechanism 14 includes a canister body 16 onto which a ferrule 18 is crimped. Mounted on rule 18 is a metering valve system, generally indicated at 20. Metering valve system 20 includes a valve stem 22, a portion of which is disposed in a valve member 24. Both valve stem 22 and valve member 24 are located in a valve housing 26, in which valve stem 22 is axially reciprocable against the action of a spring 28 which biases valve stem 22 towards a closed position, as shown in FIG.

[0050] The metering valve system 20 further comprises a metering chamber 30 defined by the valve member 24 and a portion of the valve stem 22 along with an inner seal 32 and an outer seal 34. The inner seal 32 acts to seal the valve member 24 to the valve housing 26 and separates the metering chamber 30 from an interior 36 of the valve housing 26. The outer seal 34 acts to seal the valve member 24 and the valve housing 26 to the ferrule 18, which in turn seals the metering chamber 30 from the exterior of the pressurized drug container mechanism 14. A further seal is provided by a can body seal 42 which acts to seal the can body 16 to the ferrule 18 when the ferrule 18 is crimped. The valve housing 26 has a number of slots 38 which allow the interior 36 of the valve housing 26 to communicate with the interior 40 of the can body 16. The valve stem 22 has two channels 44, 46. Each of the channels 44, 46 comprises a vertical passage and a horizontal passage. The cross passage of the valve stem channel 44 is arranged such that when the pressurized drug container mechanism 14 is in its closed position as shown in Figure 1, the metering chamber 30 is in communication with the interior 36 of the valve housing 26, and therefore also with the interior 40 of the canister body 16. As will be explained in more detail below, the volume of the metering chamber 30 corresponds to the volume of drug-containing fluid to be administered in a single dose. In the closed position shown in Figure 1, the dose is contained entirely within the metering chamber 30 and cannot escape outside the pressurized drug container mechanism 14 due to the action of the exterior seal 34.

[0051] To expel a dose of drug-containing fluid, the valve stem 22 is forced against the biasing action of the spring 28 toward the inside 36 of the valve housing 26 to the extent that the valve stem channel 44 is no longer in communication with the metering chamber 30. In this dispensing position, the valve stem 22 is designed such that the valve stem channel 46 of the valve stem 22 is in communication with the metering chamber 30, thereby allowing the dose of drug-containing fluid in the metering chamber 30 to be dispensed by the valve stem 22. The dose then passes through the passage 12e, the opening 12f and the aperture passage 12b. and exit the device.

[0052] When the valve stem 22 is then released, the biasing action of the spring 28 urges the valve stem 22 back towards the position shown in Figure 1. Thus, the valve stem channel 46 assumes a position in which the metering chamber 30 is sealed against the outside, and the valve stem channel 44 assumes a position in which the interior 36 of the valve housing 26 communicates with the metering chamber 30. Due to the pressure differential between the relatively high pressure interior 40 of the canister body 16 and the relatively low pressure metering chamber 30, the metering chamber 30 is refilled with another dose of drug-containing fluid.

[0053] The pressurized dispenser device 10 shown in Figure 1 is one example of such a device, and many other metering arrangements are known that differ more or less in their exact mechanism of action. The present invention does not claim the mechanism of action of the device shown in Figure 1 or any other pressurized dispenser device. Instead, the present invention provides devices and components for devices that are treated to inhibit loss of medicament to the internal surfaces of the device, and related methods of producing such devices and components. The device shown in Figure 1 is provided to aid in understanding how the present invention may be applied. It will be appreciated by those skilled in the art that the present invention may be applied to pressurized dispenser device designs other than that shown in Figure 1, and indeed to different types of medicament dispenser devices than the pressurized dispenser device.

[0054] The present invention provides a method for depositing a coating that inhibits drug loss to the interior surface of a pressurized dispensing device by providing a highly crosslinked plasma polymerized coating. The inventors have found that coatings with higher crosslink density can be deposited much thinner than those with lower crosslink density while still achieving optimal barrier properties. Figure 2 shows an arrangement in which a can body 50 is coated by plasma deposition. In this arrangement, the can body 50 is maintained at ground and an elongated RF electrode 52 extends inside the can body 50 substantially along the longitudinal axis of the can body 50. The can body 50 is positioned within a plasma reactor 54 having a gas / monomer supply inlet 56 and an outlet 58 that exhausts gas using a vacuum pump (not shown). A suitable monomer or monomers are delivered to the can body 50 by the gas inlet 56 from a suitable delivery source (not shown), typically including one or more mass flow regulators. The gas inlet 56 is preferably 0.01 W / cm 2 ~0.05W / cm 2 in the range of 0.02 W / cm 2 or 0.03 W / cm 3 These relatively low power densities are beneficial to the coating deposition rate and also increase the crosslink density of the deposited coating because re-sputtering from the coating surface and the resulting premature termination of growing polymer chains caused by high power densities are avoided.

[0055] First, oxygen and argon are flowed into the plasma reactor 54 through the gas inlet 56 to purge the plasma reactor 54. -2 mbar~2×10 0 mbar range, typically 1.3×10 0 A process pressure of 10 ... The oxygen and argon supplies are maintained at constant flow rates, and the process pressure is also maintained. Power is supplied to the RF electrode 52, and a plasma is struck using techniques known in the art. The interior surface of the can body 50 is pre-cleaned with a mixture of argon and oxygen using both reactive ion etching and sputtering to remove any pre-processing hydrocarbons, organic constituents, and surface inspirations from the surface of the component. The process is controlled using a DC bias voltage greater than 50 volts, preferably greater than 150 volts. The resulting interior surface of the can body 50 is clean and functionalized to allow the subsequent carbon overlay to react and bond with the prepared surface.

[0056] Once the inside surface of the can body 50 has been cleaned, the supply of oxygen and argon to the plasma reactor 54 via the gas inlet 56 is stopped and the system is returned to a rough vacuum pressure of 1×10 -3 The plasma is then pumped down to 1000 psi (2.5 mbar) to remove residual oxygen, which may be detrimental to the structure and adhesion of the deposited coatings, since in combination with carbon it may act to reactively ion etch the deposited coatings to form CO and CO2, which are easily exhausted from the plasma reactor 54 via the gas outlet 58.

[0057] Next, a hydrocarbon precursor, such as methane, ethane, propane, butane, or pentane, is flowed into the plasma reactor 54 through the gas inlet 56, and the pressure in the plasma reactor 54 is increased to approximately 1.3×10 0 First, the flow rate of the hydrocarbon precursor is increased for a defined period of time. -2 mbar and 2×10 0Gas pressures in the mbar range can be used. These relatively high pressures increase the rate of deposition of the carbon coating. A highly crosslinked non-diamond-like carbon coating is deposited onto the inside surface of the can body 50 by striking and maintaining a plasma while flowing the hydrocarbon precursors into the can body 50. Typically, 13.56 MHz RF power is applied to the RF electrode 52 to strike a plasma using techniques known in the art. Other RF frequencies may be used, and it is expected that frequencies in the range of 4 kHz to 20 MHz may be utilized in either continuous power or pulsed modes.

[0058] When using the configuration shown in FIG. 2, the effective electrical resistance of the can body 50 increases as the inner surface of the can body 50 is progressively coated with an RF electrode 52 positioned on the grounded can body 50. As a result, the normal electron path to the grounded can body 50 is reduced as the coating thickness increases. Forward power operation is typically used in prior art plasma polymerization processes for coating components such as can bodies for drug dispenser devices. However, under normal forward power operation, the electron emission from the power supply is reduced as the process progresses, the self-DC bias is reduced, and the plasma intensity drops, resulting in a loss of crosslink density that is detrimental to the coating properties and can lead to a weak, porous coating. In contrast, by manipulating the DC bias control, the DC bias is fixed and a constant electron emission is maintained which in turn maintains a constant plasma density. This provides a constant deposition rate and a very high quality uniform coating with increasing crosslink density. Additionally, the DC bias can be increased with deposition rate and time to control the thickness of the coating, both in terms of the lateral extent of the coating, and in terms of the depth of the coating, with a constant crosslink density, which would not otherwise be achieved in the forward power mode. Thus, a highly crosslinked non-diamond-like carbon coating is deposited by manipulating the DC bias control. This DC bias control provides a constant deposition rate, and a uniform coating of very high quality. This steady rate of coating can be maintained until the desired thickness is obtained. Typically, the desired thickness is in the range of 5 nm to 150 nm, and the carbon polymer coating is a highly crosslinked (at least 90%) and highly reactive coating on the surface of the can body 50. The carbon polymer layer also provides a uniform insulating layer that masks any non-uniformities on the surface of the can body 50. The interior surface of the can body 50 after application of the carbon polymer layer is free of any crosslinking due to reaction with fluorine ions in the plasma or C ions derived from the plasma. x F yEither the deposition of ions provides a uniform floating potential or charge that allows a uniform thin film of fluorocarbon to be formed in the next processing step. This uniform charge is critical for uniform deposition and cannot be achieved without the use of an insulating carbon layer.

[0059] Once the desired thickness of the highly crosslinked non-diamond-like carbon layer is obtained, fluorocarbon monomer is introduced into the can body 50 via gas inlet 56. The fluorocarbon monomer may be introduced immediately following a cut-off in the hydrocarbon monomer feed or may be introduced after carbonization. The fluorocarbon monomer may be mixed with hydrogen monomer or may be increased over time. It is preferable to decrease the hydrocarbon monomer feed while increasing the fluorocarbon monomer feed over time so that the interface between the carbon layer and the fluorocarbon polymer layer is gradual, i.e. there is no clear boundary between these two layers. The highly reactive carbon polymer coating already deposited on the inner surface of the can body 50 reacts with the free fluorine generated in the fluorocarbon plasma, resulting in a fluorocarbon layer that instantly covers the carbon layer. Furthermore, this step is accompanied by a significant decrease in the DC bias, which prevents etching of the carbon layer. The pressure in the plasma reactor 54 is increased to 9×10 -1 mbar~1.3×10 0 The relatively high pressure, maintained at 1000 psi, compared to prior art processes, results in an increased rate of formation of the fluorocarbon layer.

[0060] The fluorocarbon layer is deposited until a minimum thickness is obtained. Typically, the thickness of the fluorocarbon layer ranges from 1 nm to 15 nm when using CF4 as the hydrocarbon precursor, or approximately 16 nm to 100 nm when using C4F8 as the hydrocarbon precursor. Without a highly crosslinked carbon barrier layer deposited on the surface of the can body 50, a fluorocarbon layer having a thickness of 1 nm to 15 nm, or even 1 nm to 100 nm, is clearly not sufficient to form a complete barrier alone. Also, the fluorine to carbon ratio in the fluorocarbon layer is typically much higher than that observed in a straight fluorocarbon plasma process (1.5:1 to 1.95:1 compared to 1:1 to 1.5:1), resulting in a high CF2 content. This achieves a hydrophobic water-repellent surface with high barrier properties that come into contact with the drug during storage and use of the device. The resulting carbon polymer layer deposited on the inside surface of the can body 50 and the fluorocarbon polymer deposited on the surface of the hydrocarbon polymer layer results in a highly covalent integral coating that exhibits inherently strong cohesive properties that are impermeable to HFA and other organic solvents.

[0061] Once the fluorocarbon polymer layer has reached the desired thickness, the supply of fluorocarbon monomer to the plasma reactor via gas inlet 56 is stopped and the system is returned to a low vacuum pressure of 1×10 -3 The gas is then evacuated to mbar to remove any residual monomer via gas outlet 58.

[0062] Aluminum can bodies coated using the above method show water contact angles of 115 degrees to 130 degrees. XPS spectra of the coatings show that the carbon polymer layer has an O2 content of less than 2% and the fluorocarbon polymer layer has an O2 content of less than 1%. The XPS spectra also show at least 95% crosslinking in the carbon coating when precursors such as methane, ethane and ethylene are used, and greater than 55% crosslinking in the fluorocarbon polymer layer.

[0063] The fluorocarbon monomers used as precursors for the fluorocarbon polymer layer are preferably small due to their high fluorine to carbon ratio. The monomers are preferably either CF4 or C4F8, although other suitable precursors include C2F6, C3F8, C5H 10 , HFA134a, HFA227 or HFA152a. The hydrocarbon precursor can be any hydrocarbon monomer including methane, ethane, propane, butane, pentane, hexane, and the like. EXAMPLES

[0064] Example 1 Using the arrangement shown in Figure 2 and described above, a coating was deposited on the inside surface of an aluminum can body that inhibits drug loss to the interior surface of the can body by providing a highly crosslinked plasma deposited coating. Table 1 shows the process conditions at various stages of surface modification of an aluminum can body according to an exemplary embodiment of the present invention.

[0065] [Table 1]

[0066] Random samples of canisters having coatings formed by the above method were subjected to a copper sulfate test to inspect the coating integrity. During the copper sulfate test, each canister was filled to the brim level with acidified CuSO4 and allowed to stand for one minute. The CuSO4 was then removed, the canisters were opened, and the level of copper sulfate reaction was visually analyzed and graded. Evidence of copper sulfate reaction is easy to identify, as aluminum turns black upon exposure to acidified CuSO4 due to copper precipitation at the exposed aluminum sites.

[0067] Figure 3A shows an aluminum canister with a coating of high integrity, i.e., without small pores, that had a negative reaction with copper sulfate. Figure 3B shows an aluminum canister that underwent a fine particle reaction with copper sulfate due to the presence of small pores. Figure 3C shows an aluminum canister that underwent a partial reaction with copper sulfate due to a coating with low integrity. Figure 3D shows an aluminum canister without a coating that underwent a complete reaction with copper sulfate.

[0068] The images show that if the coating is deposited without the correct level of cross-linking by plasma means, or if the coating density is not sufficient, the integrity of the coating is significantly compromised as seen by pin holing and high levels of aluminum attack. All canisters having coatings formed by the above method exhibited high integrity coatings that did not react with acidified copper sulfate, i.e., the canisters corresponded to the canister shown in Figure 3A.

[0069] Example 2 The process described in Example 1 was then repeated using CF4 instead of C4F8 as the fluorocarbon precursor. When using CF4 as the fluorocarbon precursor, it is possible to deposit a thinner fluorocarbon polymer layer of 1 nm to 15 nm that has comparable hydrophobic barrier properties to the fluorocarbon polymer layer (60 nm to 100 nm) produced using C4F8 as the fluorocarbon precursor. This is due to the higher fluorine to carbon ratio. The XPS data for each of the coatings is compared in Table 2 below.

[0070] [Table 2]

[0071] Each of the coatings produced contained less than 1% O. Each of the coatings had a fluorine-to-carbon ratio of 1.3 to 1.5.

[0072] The carbon 1s spectra for each of the canister coatings are compared in Table 3.

[0073] [Table 3]

[0074] It can be seen that when CF4 is used as the fluorocarbon precursor, there is a much higher CF2:CF3 ratio. Without wishing to be bound by any theory or speculation, the inventors believe that this is due to either an increase in polymer chain length or an increase in the proportion of free fluorine in the plasma that reacts with the carbon barrier underlayer.

[0075] From the above description, it is clear to those skilled in the art that modifications and changes can be made to the described embodiments without departing from the scope of the present invention as defined in the claims.For example, the highly crosslinked non-diamond-like carbon barrier layer does not need to be coated with a fluorocarbon layer.Instead, the carbon layer can be coated with a silicon layer, or indeed any hydrophobic or other layer.Alternatively, the highly crosslinked non-diamond-like carbon barrier layer can be used alone to effectively prevent drug absorption onto the surface of the device, and no top layer or coating is required.

[0076] Additionally, while this embodiment discloses coating the aluminum can body, the coating may be deposited on any polymeric or metallic component used to distribute the drug, providing an effective barrier to prevent absorption of the drug onto the surface of the component.

Claims

1. 1. A method of treating a component of a medicament dispenser device comprising at least one surface that will come into contact with medicament during storage or use of the device, comprising: providing said components; coating at least one of said surfaces with a coating comprising a crosslinked non-diamond-like carbon layer containing up to 50 At % hydrogen and having an interface with at least one surface of the device; Including, the carbon layer is at least 80% cross-linked; At least a portion of the coating step is in the range of 0.01 W / cm 2 ~0.05 W / cm 2 The method is performed using a power density of

2. The method of claim 1 , wherein the carbon layer is formed by a plasma treatment process that includes generating a plasma of at least one hydrocarbon monomer.

3. 3. The method of claim 1 or 2, wherein the coating comprises a second layer that comes into contact with the agent during storage or use of the device, the second layer being formed by plasma deposition.

4. The method of any one of claims 1 to 3, wherein at least a portion of the coating step is performed under DC bias control.

5. the coating comprises a second layer that comes into contact with the agent during storage or use of the device, the second layer being formed by plasma deposition; 5. The method of claim 4, wherein the plasma treatment step and the plasma deposition of the second layer are performed under DC bias control, the plasma treatment step being performed using a higher DC bias voltage than the plasma deposition of the second layer.

6. At least a portion of the coating step is in the range of 0.02 W / cm 2~0.03 W / cm 2 The method of any one of claims 1 to 5, wherein the method is carried out using a power density of

7. A dispenser device for dispensing a medicament, the device comprising at least one component having a coating on at least one surface thereof, the coating comprising a crosslinked non-diamond-like carbon layer having an interface with an underlying surface of the component and a second layer which comes into contact with the medicament during storage or use of the device; the carbon layer contains up to 50 At % hydrogen and the cross-linking in the carbon layer is at least 80%; A dispenser device, wherein the second layer is a plasma polymerized polymer layer.

8. The dispenser device of claim 7, wherein the carbon layer contains up to 10 At % hydrogen.

9. 9. The dispenser device of claim 7 or 8, wherein the cross-linking in the carbon layer is at least 90%.

10. A dispenser device as described in claim 7 or 8, wherein the cross-linking in the carbon layer is at least 95%.

11. A dispenser device according to any one of claims 7 to 10, wherein said carbon layer has a thickness of between 5 nm and 150 nm.

12. A dispenser device described in any one of claims 7 to 10, wherein the carbon layer has a thickness of 50 nm to 150 nm.

13. A dispenser device according to any one of claims 7 to 12, wherein said carbon layer comprises less than about 3 At % oxygen as measured by XPS.

14. A dispenser device as described in any one of claims 7 to 12, wherein the carbon layer contains less than about 2At% oxygen as measured by XPS.

15. A dispenser device as described in any one of claims 7 to 12, wherein the carbon layer contains less than about 1 At% oxygen as measured by XPS.

16. A dispenser device according to any one of claims 7 to 15, wherein said at least one component is made from aluminium.

17. 8. A component for a dispenser device as described in claim 7, the component comprising a coating on at least one surface thereof, the coating comprising a carbon layer having an interface with the underlying surface of the component and a second layer that comes into contact with the medicament during storage or use of the device.

Citation Information

Patent Citations

  • Drug delivery devices

    EP1066073A1

  • Film for pharmaceutical container

    JP1999070152A

  • Coating jet plasma deposition method and apparatus, and coating thereof

    JP2001514328A

  • Gas barrier film, method for manufacturing the same and vacuum heat insulating body using gas barrier film

    JP2002225170A

  • Metered-dose inhaler canister coated more than once with fluorocarbon polymer

    JP2004509031A